Korean Immigrants in Canada : Perspectives on Migration, Integration, and the Family - Noh, Marianne S., 1977-; Kim, Ann H., 1972-; Noh, Samuel, 1946- (Book collections on Project MUSE., 2012)
"Koreans are one of the fastest-growing visible minority groups in Canada today. However, very few studies of their experiences in Canada or their paths of integration are available to public and academic communities. Korean Immigrants in Canada provides the first scholarly collection of papers on Korean immigrants and their offspring from interdisciplinary, social scientific perspectives. The contributors explore the historical, psychological, social, and economic dimensions of Korean migration, settlement, and integration across the country. A variety of important topics are covered, including the demographic profile of Korean-Canadians, immigrant entrepreneurship, mental health and stress, elder care, language maintenance, and the experiences of students and the second generation. Readers will find interconnecting themes and synthesized findings throughout the chapters. Most importantly, this collection serves as a platform for future research on Koreans in Canada."--